Usefulness of colposcopy, cytology and histopathology on patients with cervical polyps - Kłosinski, Witold; Wieczorek, Marek; Lau, Katarzyna; Rżanek, Anna; Bobeff, Artur; Rutkowska, Beata; Jędrzejczyk, Sławomir (Menopause Review/Przegląd Menopauzalny, 2009)
Background: Cervical polyps are common purpose of unidentified discharge from the reproductive tract which are main complaints of patients visiting gynecologist. Colposcopy, cytology and histopathology are main diagnostic components which are use in cervical diagnostic. The aim of this study was to estimate the usefulness of cytology and colposcopy on patients with cervical polyps. Second purpose was to detect other cervical abnormalities accompanying cervical polyps. Material and methods: In our study we included 75 preoperative female patients aged between 24-80 years old. We performed cervical smear and colposcopic examination to all patients. The results are compared with histopathology outcome which we received from D&C and colposcopic guided cervical biopsy. Results: In the examined group 10 patients (40%) presented unidentified, recurring infections of reproductive tract compared with 5% of control group. We have not verified any abnormal cytological outcome on patients with cervical polyps. We noticed often low grade dysplasia (CIN I), acetowhite epithelium and Nabothian follicle on patient from examined group, then in control. Conclusions: Cervical polyps are very common abnormalities which can be connected with some others abnormalities. It is important result that low grade dysplasia is more often on patients with cervical polyps.